The impact of social media on the image of a company - Krasochenko, K.; Petrenko, O. (НТУ ДП, 2022)
The growing usage of social media today is affecting many spheres of life including business and the means of running it. It goes without saying that social media is a powerful tool for promoting business, boosting brand awareness, and shaping a positive brand image. The role of social media in building a company image is crucial nowadays. A key feature of social media is its openness. Social media provide a virtual network place where people can enjoy expressing their opinions, exchange opinions, share experiences, and publish and control messages anywhere anytime
Keywords: social media; business; media